2010
DOI: 10.4028/www.scientific.net/amr.152-153.288
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Polyphosphoric Acid (PPA) Modified Asphalt Binders

Abstract: Polyphosphric acid (PPA) modified asphalt binders were produced in the laboratory using one base asphalt and four levels of PPA contents (0.6%, 1.0%, 1.5% and 2.0% by weight of base asphalt). Penetration test, softening point test, rotation viscosity test, creep test with bending beam rheometer (BBR) and four components test were carried out to study the performance of PPA modified asphalt binders and possible modification mechanism. The results indicate that the high-temperature performance of PPA modified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…e phase angle decrease is due to the fact that PPA made the corn stalk bioasphalt/PPA composite modified asphalt more elastic. e phase angle decrease shows that it increases the asphalt's rebound rate under load, thereby improving the asphalt's high-temperature stability [33,34].…”
Section: Temperature Scanningmentioning
confidence: 99%
“…e phase angle decrease is due to the fact that PPA made the corn stalk bioasphalt/PPA composite modified asphalt more elastic. e phase angle decrease shows that it increases the asphalt's rebound rate under load, thereby improving the asphalt's high-temperature stability [33,34].…”
Section: Temperature Scanningmentioning
confidence: 99%
“…A developed liquid anti-aging agent, which was used for the anti-aging of asphalt binder in an original sample, consisted of oil antioxidant, polyphosphoric acid (PPA) and SBS-modified asphalt binder. These three components effectively inhibited the oxidation reaction of asphalt binder in service through synergistic effects [17]. An oil antioxidant mainly provides anti-aging properties, which significantly improves the low-temperature performance and fatigue anti-cracking properties of virgin asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
“…Baldino et al [10] found that the glass transition temperature decreased when PPA was mixed into asphalt, which could improve the stiffness, thus improving the low-temperature performance. However, Cao et al [11] obtained conflicting conclusions that PPA can reduce low-temperature performance, and it is proved by Cao et al [12] that PPA has little impact on its low-temperature performance.…”
Section: Introductionmentioning
confidence: 99%